A tunable immitance simulator with a voltage differential current conveyor - Metin, Bilgin; Atasoyu, Mesut; Arslan, Emre; Herencsar, Norbert; Cicekoglu, Oguzhan (IEEE, 2017)
In this paper, an electronically tunable immitance circuit is proposed. The presented circuit can be configured as a tunable grounded inductor or capacitor multiplier. The proposed circuit employs a single active element called Voltage Differential Current Conveyor, a single resistor and a single capacitor. The presented circuit does not require element matching constraints. It is linearly tunable over four decades of frequency using bias current control. Simulation results are included to verify theory.
Keywords: active filter; immitance; Current conveyor; inductance simulator